Frosting Effect on Potato and its management - Singh, S. P.; Sadawarti, Murlidhar J.; Pandey, K. K.; Singh, B. P. (Indian Farming, 2015)
Potato is very much susceptible to frost which is an abiotic constraintcausing severe yield losses. Frost damage also affects growth ofnucleus and breeder seed potato crops under irrigated conditions. The effectiveness of furrow irrigation has been reported to prevent frost damage in potato to a large extent.